MicroRNA214 expression inhibits HCC cell proliferation through PTK2b/ Pyk2 - Chen, Cui; Tao, Zhen; Li, Ya; Li, Jie; Xu, Yang (Cellular and Molecular Biology, 2022)
MicroRNAs (miRNAs/miRs) are crucial regulatory molecules that act as the most significantly downregulated microRNAs in hepatocellular carcinoma (HCC). PTK2b/Pyk2 is a non-receptor protein tyrosine kinase, which plays an important role in the development and metastasis of cancer. In this study, we explored the expression level and functional relationship between MicroRNA-214 (miR-214) and PTK2b/ Pyk2 in liver cancer cells. For this purpose, we analyzed the expression of miR-214 and PTK2b/Pyk2 in 38 cases of HCC and paired non-neoplastic tissue specimens using real-time PCR. MTT, cell cycle and construct recombinant plasmids analysis were used to explore the effects of miR-214 and PTK2b/Pyk2 on liver cancer cell proliferation. Results showed that the expression level of mir-214 in liver cancer tissues and liver cancer cell lines was significantly lower than that in normal tissues and cells, while the expression of PTK2b/Pyk2 was significantly increased. The overexpression of mir-214 or inhibition PTK2b/Pyk2 inhibited the proliferation of HCC cells. This research showed that mir-214 has an inhibitory effect on liver cancer through the expression of PTK2b/Pyk2.